Klövform och klövsjukdomar hos intensivt uppfödda köttrastjurar - Björkroth, Martin (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
The top selection of Swedish beef bulls are evaluated yearly by Svensk Köttrasprövning AB at Gismestad. The bulls are selected from six different breeds; Angus, Blonde d´Aquitaine, Charolais, Hereford, Limousin and Simmental, and are kept on straw bedding apart from a concrete alley in front of the feeding area during the six months of evaluation period. The bulls are evaluated according to their fertility scores, growth, exterior and temperament and the exterior, body posture and claw conformation reflect important qualities for their longevity. In spite of good values for fertility, it has been noticed in the last years that the fertility results and longevity have been unsatisfactory and claw and/or bone disorders have been suspected as a contributory cause.